2019
DOI: 10.1142/s1793962319410071
|View full text |Cite
|
Sign up to set email alerts
|

The Petrov–Galerkin finite element method for the numerical solution of time-fractional Sharma–Tasso–Olver equation

Abstract: In this paper, time-fractional Sharma–Tasso–Olver (STO) equation has been solved numerically through the Petrov–Galerkin approach utilizing a quintic B-spline function as the test function and a linear hat function as the trial function. The Petrov–Galerkin technique is effectively implemented to the fractional STO equation for acquiring the approximate solution numerically. The numerical outcomes are observed in adequate compatibility with those obtained from variational iteration method (VIM) and exact solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Referring to the relevant literature, 6,13,14 it can be found that the process of solving the exact solution of the STO equation is complex, and the application flexibility of these methods is poor. In addition, traditional numerical solution methods, such as the finite difference (FD) method 16 and the finite element (FE) method 17 also be considered to study the kind of equation. However, traditional methods are difficult to handle complex boundary conditions, and their iterative format is sophisticated.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the relevant literature, 6,13,14 it can be found that the process of solving the exact solution of the STO equation is complex, and the application flexibility of these methods is poor. In addition, traditional numerical solution methods, such as the finite difference (FD) method 16 and the finite element (FE) method 17 also be considered to study the kind of equation. However, traditional methods are difficult to handle complex boundary conditions, and their iterative format is sophisticated.…”
Section: Introductionmentioning
confidence: 99%